Adaptive capabilities of the nervous system : proceedings of the 11th International Summer School of Brain Research - McConnell, P. S.; Boer, Gerard J.; Romijn, Herms, 1940-; Poll, Nanne E. van de; Corner, M. A. (Michael Alan), 1933- (Progress in brain research, 1980)
Adaptive Capabilities of the Nervous System.